Exercise Ameliorates Endocrine Pancreas Damage Induced by Chronic Cola Drinking in Rats. - Matilde Otero-Losada; Julián González; Angélica Müller; Graciela Ottaviano; Gabriel Cao; Francisco Azzato; Giuseppe Ambrosio; José Milei (PLoS ONE, 2016)
Purpose This study evaluates whether the daily practice of an exercise routine might protect from endocrine pancreas damage in cola drinking rats. Methods Forty-eight Wistar rats were randomly assigned to 4 groups depending on a) beverage consumption ad libitum, water (W) or cola beverage (C), and b) physical activity, sedentary (S) or treadmill running (R). Accordingly, 4 groups were studied: WS (water sedentary), WR (water runner), CS (cola sedentary) and CR (cola runner). Body weight, nutritional data, plasma levels of glucose, creatinine, total cholesterol and cholesterol fractions, and triglycerides (enzymocolorimetry), and systolic blood pressure (plethysmography) were measured. After 6 months, euthanasia was performed (overdose sodium thiopental). Pancreatic tissue was immediately excised and conventionally processed for morphometrical and immunohistochemical determinations. Results The effects of running and chronic cola drinking on pancreas morphology showed interaction (p<0.001) rather than simple summation. Cola drinking (CS vs WS) reduced median pancreatic islet area (-30%, 1.8 10(4) μm2 vs 2.58 10(4) μm2, p<0.0001) and median β-cell mass (-43%, 3.81 mg vs 6.73 mg, p<0.0001), and increased median α/β ratio (+49%, 0.64 vs 0.43, p< 0.001). In water drinking rats (WR vs WS), running reduced median α-cell mass (-48%, 1.48 mg vs 2.82 mg, p<0.001) and α/β ratio (-56%, 0.19 vs 0.43, p<0.0001). Differently, in cola drinking rats (CR vs CS), running partially restored median islet area (+15%, 2.06 10(4) μm2 vs 1.79 10(4) μm2, p<0.05), increased median β-cell mass (+47%, 5.59 mg vs 3.81 mg, p <0.0001) and reduced median α/β ratio (-6%, 0.60 vs 0.64, p<0.05). Conclusion This study is likely the first reporting experimental evidence of the beneficial effect of exercise on pancreatic morphology in cola-drinking rats. Presently, the increase of nearly 50% in β cells mass by running in cola drinking rats is by far the most relevant finding. Moderate running, advisably indicated in cola consumers and patients at risk of diabetes, finds here experimental support.